2019
DOI: 10.1002/mrm.27892
|View full text |Cite
|
Sign up to set email alerts
|

Coil profile estimation strategies for parallel imaging with hyperpolarized 13C MRI

Abstract: Purpose To investigate auto‐ and pre‐calibration coil profile estimation for parallel imaging reconstruction of hyperpolarized 13C MRI volumetric data. Methods Parallel imaging reconstruction was studied with 3 different approaches for coil profile estimation: auto‐calibration, phantom calibration, and theoretic calibration. Acquisition was performed with a 3D stack‐of‐spirals sequence with spectral–spatial excitation and Cartesian undersampling. Parallel imaging reconstructions were done with conjugate gradie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…The duration of the combined excitation and readout was 70 ms 30 × 30 × 16 cm 3 reconstructed FOV, at a 5 × 5 × 10 mm 3 nominal resolution, achieved in 4 excitations with a spiral readout duration of 45 ms. 23 All data were acquired on an MR750 3T scanner (GE Healthcare, Waukesha, WI) with a locally built, fixed-geometry coil setup consisting of a linearly polarized 13 C volume coil for transmission and a rigid 12-element array for reception. 24 The 12 receive elements (with 130 mm diameter) were distributed in 2 rows mounted over a cylinder with a diameter of 300 mm. The receive array and coil setup are shown in Supporting Information Figure S1.…”
Section: F I G U R Ementioning
confidence: 99%
See 4 more Smart Citations
“…The duration of the combined excitation and readout was 70 ms 30 × 30 × 16 cm 3 reconstructed FOV, at a 5 × 5 × 10 mm 3 nominal resolution, achieved in 4 excitations with a spiral readout duration of 45 ms. 23 All data were acquired on an MR750 3T scanner (GE Healthcare, Waukesha, WI) with a locally built, fixed-geometry coil setup consisting of a linearly polarized 13 C volume coil for transmission and a rigid 12-element array for reception. 24 The 12 receive elements (with 130 mm diameter) were distributed in 2 rows mounted over a cylinder with a diameter of 300 mm. The receive array and coil setup are shown in Supporting Information Figure S1.…”
Section: F I G U R Ementioning
confidence: 99%
“…It has been demonstrated that loading effects have minimal effect on coil-sensitivity profiles at the carbon frequency at 3 T. 24 For fixed coil geometry, this enables the use of precalibrated sensitivity profiles in parallel imaging reconstruction of undersampled 13 C data. In this study, precalibration was based on simulated complex sensitivity profiles of the 12-element receive array by means of CST (Darmstad, Germany) RF modeling.…”
Section: F I G U R Ementioning
confidence: 99%
See 3 more Smart Citations